Multi-modal feature selection with anchor graph for Alzheimer's disease - Li, Jiaye; Xu, Hang; Yu, Hao; Jiang, Zhihao; Zhu, Lei (Frontiers in Neuroscience, 2022)
In Alzheimer’s disease, the researchers found that if the patients were treated at the early stage of the disease, it could effectively delay the development of the disease. At present, multi-modal feature selection is widely used in the early diagnosis of Alzheimer’s disease. However, existing multi-modal feature selection algorithms focus on learning the internal information of multiple modalities. They ignore the relationship between modalities, the importance of each modality and the local structure in the multi-modal data. In this paper, we propose a multi-modal feature selection algorithm with anchor graph for Alzheimer’s disease. Specifically, we first use the least square loss and l2;1−norm to obtain the weight of the feature under each modality. Then we embed a modal weight factor into the objective function to obtain the importance of each modality. Finally, we use anchor graph to quickly learn the local structure information in multi-modal data. In addition, we also verify the validity of the proposed algorithm on the published ADNI dataset.